Advances in the treatment of pulmonary nodules - Zhang, Quncheng; Wu, Xuan; Yang, Huizhen; Luo, Peiyuan; Wei, Nan; Wang, Shuai; Zhao, Xingru; Wang, Ziqi; Herth, Felix; Zhang, Xiaoju (Respiration, 2024)
BACKGROUND: Early detection and accurate diagnosis of pulmonary nodules are crucial for improving patient outcomes. While surgical resection of malignant nodules is still the preferred treatment option, it may not be feasible for all patients. We aimed to discuss the advances in the treatment of pulmonary nodules, especially stereotactic body radiotherapy (SBRT) and interventional pulmonology technologies, and provide a range of recommendations based on our expertise and experience. - SUMMARY: Interventional pulmonology is an increasingly important approach for the management of pulmonary nodules. While more studies are needed to fully evaluate its long-term outcomes and benefits, the available evidence suggests that this technique can provide a minimally invasive and effective alternative for treating small malignancies in selected patients. We conducted a systematic literature review in PubMed, designed a framework to include the advances in surgery, SBRT, and interventional pulmonology for the treatment of pulmonary nodules, and provided a range of recommendations based on our expertise and experience. - KEY MESSAGES: As such, alternative therapeutic options such as SBRT and ablation are becoming increasingly important and viable. With recent advancements in bronchoscopy techniques, ablation via bronchoscopy has emerged as a promising option for treating pulmonary nodules. This study reviewed the advances of interventional pulmonology in the treatment of peripheral lung cancer patients that are not surgical candidates. We also discussed the challenges and limitations associated with ablation, such as the risk of complications and the potential for incomplete nodule eradication. These advancements hold great promise for improving the efficacy and safety of interventional pulmonology in treating pulmonary nodules.